TINDAK TUTUR ILOKUSI DALAM VIDEO PRESENTASI PELUNCURAN PRODUK MOBIL HYUNDAI MOTOR: KAJIAN PRAGMATIK - Zihan Fauzia, - (2020)
This research discussed illocutionary speech acts in a presentation video on the launch of Hyundai Motor's car products. This research aimed to identify and describe speech act forms, speech act strategies, and speech markers in a presentation video on the launch of Hyundai Motor's car products. This research was conducted because Korean Language Education students, especially those who took KSP (Korean for Specific Purpose) concentrations, encountered difficulties when delivering a presentation using Korean. The method used in this research was descriptive qualitative by collecting data in the form of speaker's illocutionary speech in Hyundai Motor's car product presentation, identifying speech types, markers, and strategies, and then describing them descriptively. The assertive speech acts were found the most often in this research. Assertive speech acts were the most important speech acts used in product launch presentation activities because they expressed the advantages or information on the features of the products being offered. Speech context played an important role in identifying speech acts in this research.